Magnetic anisotropy and spin scattering in (La2/3Sr1/3)MnO3/CaRuO3 bilayers - Purnima P. Balakrishnan; Emily Lindgren; Margaret Kane; Jacob J. Wisser; Yuri Suzuki (AIP Advances, 2021)
Complex ferromagnetic oxides have been identified as possible candidate materials for sources of spin currents. Here we study bilayers of ferromagnetic (La2/3Sr1/3)MnO3 (LSMO) and metallic CaRuO3 (CRO) on LSAT substrates as a model system for spin pumping. Ferromagnetic resonance (FMR) measurements of these bilayers show evidence of spin pumping across the interface in the form of an increase in Gilbert damping with the addition of CRO. FMR indicates that the presence of CRO modifies the magnetic anisotropy of the LSMO. By increasing CRO thickness, we find a reduction of the out-of-plane anisotropy and simultaneous rotation of the easy axis within the plane, from the ⟨110⟩ to ⟨100⟩ axis. The evolution of magnetic anisotropy determined by FMR disagrees with that measured by bulk SQUID magnetometry and is accompanied by structural distortions in the LSMO layer as measured by x-ray diffraction, thus suggesting a change in magnetic anisotropy attributed to structural distortions imposed on LSMO by CRO. These results suggest that while LSMO and CRO remain promising candidates for efficient pure spin current generation and detection, respectively, epitaxial integration of perovskites will cause additional changes which must be accounted for in spintronics applications.